Effect of Al Addition on Electrochemical Behavior of Sn-0.7Cu-xAl Lead-Free Solders Alloys in 3.5 wt.% NaCl Solution - Jaiswal D.; Pathote D.; Singh V.; Behera C.K. (My University, 2025)
The corrosion behavior of alloys is highly significant as far as lead-free solder applications are concerned. The corrosion performance of the alloy is dependent mainly on the composition of the alloys. In this investigation, the effect of Al adding on the electrochemical behavior of Sn0.7Cu-xAl (x = 0, 1, 2 and 3 wt. percent) lead-free solders has been investigated using electrochemical techniques in neutral 3.5 wt.% NaCl solution at ambient temperature. The influence of aluminum additions on the microstructure of Sn-0.7Cu-xAl lead-free solder alloys was also examined. The microstructure shows that the β-Sn, eutectic and intermetallic compound (IMC) are present in the Sn-Cu-Al solder alloys. At the same time, the addition of aluminum refined the microstructure of the Sn-0.7Cu alloys. Cu6Sn5 is the interfacial IMC at the β-Sn border in the Sn-0.7Cu-xAl, while Al2Cu is the interfacial IMC in the Sn-0.7Cu-xAl. Electrochemical impedance spectroscopy (EIS) results indicate that the corrosion product layer was affected by Al addition, which changed the electrochemical corrosion behavior from charge transfer to diffusion control. By adding just 1 wt.% of Al to Sn-0.7Cu solder, the microstructure was refined, and corrosion resistance was improved, as shown by decreased corrosion current density (Icorr) and increased total resistance (Rt). Excess Al addition (above 1 wt.%) led to Al-containing IMCs, which were verified as Al2Cu, worsening the corrosion resistance of Sn-0.7Cu-xAl solders. The primary corrosion products were verified as Sn21Cl16(OH)14O6 combined with a small quantity of oxide/chloride of Sn compounds. © 2022, ASM International.